2022
DOI: 10.3390/biom12101466
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Structural Characterization of Chi-Class Glutathione Transferases: A Snapshot on the Glutathione Transferase Encoded by sll0067 Gene in the Cyanobacterium Synechocystis sp. Strain PCC 6803

Abstract: Glutathione transferases (GSTs) constitute a widespread superfamily of enzymes notably involved in detoxification processes and/or in specialized metabolism. In the cyanobacterium Synechocsytis sp. PCC 6803, SynGSTC1, a chi-class GST (GSTC), is thought to participate in the detoxification process of methylglyoxal, a toxic by-product of cellular metabolism. A comparative genomic analysis showed that GSTCs were present in all orders of cyanobacteria with the exception of the basal order Gloeobacterales. These en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…The active site, located in a cleft between both domains, contains a GSH-binding site and a hydrophobic-substrate binding site. Based on their amino-acid sequence, GSTs were classified into various classes designated by a Greek letter [ 8 , 220 ]. GSTs having a sequence identity greater than 40% or lower than 25% belong to the same class or different classes, respectively [ 215 ].…”
Section: Importance Of the Evolutionary-conserved Glutathione-s-trans...mentioning
confidence: 99%
See 2 more Smart Citations
“…The active site, located in a cleft between both domains, contains a GSH-binding site and a hydrophobic-substrate binding site. Based on their amino-acid sequence, GSTs were classified into various classes designated by a Greek letter [ 8 , 220 ]. GSTs having a sequence identity greater than 40% or lower than 25% belong to the same class or different classes, respectively [ 215 ].…”
Section: Importance Of the Evolutionary-conserved Glutathione-s-trans...mentioning
confidence: 99%
“…That human orthologs of Sll1147 could rescue the stress tolerance of a Synechocystis PCC 6803 mutant lacking Sll1147 showed that the function of this MAPEG-type GST has been conserved during evolution from cyanobacteria to humans. The chi-class GST Sll0067 and its orthologs have been characterized biochemically from Thermosynechococcus elongatus BP-1, Synechococcus elongatus PCC 6301 and Synechocystis PCC 6803 [ 214 , 220 , 223 , 227 ]. Sll0067 purified from a recombinant E. coli strain as homo-dimer composed of about 20 kDa subunit appeared to have a good GSH-transferase activity with isothiocyanates (especially phenethyl isothiocyanate) and a low activity with the model substrate CDNB (1-chloro-2, 4-dinitrobenzene) [ 220 , 223 ].…”
Section: Importance Of the Evolutionary-conserved Glutathione-s-trans...mentioning
confidence: 99%
See 1 more Smart Citation
“…The novel oxidizing conditions necessitated the emergence of protective agents such as glutathione, and it is a reasonable assumption that the evolution of GST was first established in cyanobacteria [22]. Mocchetti et al [23] have solved the crystal structure of the chi-class GST from the cyanobacterium Synechocystis, and furthermore, they have compared it with primary structures from other species. The chiclass proteins featured a well-conserved Ser-Arg-Ala-Ser amino acid motif in the active site of the N-terminal region, but a Ser residue appeared to be non-essential for catalytic activity, as indicated by mutagenesis of the Synechocystis GST.…”
mentioning
confidence: 99%